Faktor-faktor Penentu Keterlambatan Pembangunan Jalan Lingkar Utara Kota Solok - Musra, Afriyandi (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
The development of Solok city Northern Ring Road was planned to disentangle the traffic jam in the city center as well as to develop the northern part of this city. The delay that occurred in the development of Solok city Northern Ring Road, becomes a case that triggered the interest to find out What are the Determinant Factors that Caused the Delay of Solok City Northern Ring Road Development?. Descriptive analysis was used to analyze the condition of land acquisition and land compensation. Factor analysis by the help of IBM SPSS software version 20 was used in three stages of development (preparation stage, procurement of goods/service stage, and construction implementation stage). Based on the result of the analysis, it was obtained 2 (two) determinant factors in the preparation stage, sequentially based on the highest eigenvalue, i.e. (1) the land readiness factor; and (2) the land price factor. In the procurement of goods/service stage, it was attained 3 (three) determinant factors, sequentially based on the highest eigenvalue, i.e. (1) the partner competence factor; (2) the goods/service procurement factor; and (3) funds/budgets factor. In the construction implementation stage, there were 6 (six) determinant factors of the delay, sequentially based on the highest eigenvalue,Â i.e. (1) Human Resources and the partner quality factor; (2) project administration factor; (3) nature and environment factor; (4) the project location readiness factor; (5) funds and budgets factor; and (6) construction material factor.